Crítica à organização do trabalho educativo na educação física escolar: análise de uma escola estadual do município de Feira de Santana-Bahia - Ramos, Michael Daian Pacheco (2014)
The study is part of research trying to understand the training process of students in Physical Education. Focuses the organization of educational work of PE teachers. For its realization, we start from the following scientific problem: under what pedagogical proposition of physical education teachers have been organizing their educational work and what degree of consistency, according to its design, between the theoretical and pedagogical foundations established and materialized in his practice? The overall objective was to analyze under what pedagogical proposition Physical Education teachers have been organizing their educational work and what degree of consistency between what is said and accomplished. We conducted interviews with two ( 2 ) teachers in a public school in Feira de Santana, Bahia and observed two units Term class between August and December 2013. We found that pedagogical theory that guides the Political Pedagogical Project refers to pedagogy "seize grasp," also found that this pedagogical theory manifested in the syllabus of two professors analyzed. Regarding the pedagogical approach to physical education teacher identified that 1 in your lesson plan presents elements of developmentalist approach, but in their educational action does not present an organization of the teaching and learning process, minimally unaware of the theoretical and methodological foundations that guides their practice as well as the pedagogical approach that guides his class. Have the teacher 2 shows an inconsistency between the approach she says guides her classes, and the Constructivist approach that actually materializes in their classes, the Health Promotion Therefore, the Physical Education classes observed on the theoretical frameworks presented (approaches developmental, constructivist and Health Promotion) do not present great possibilities for development and raising the cultural standard of the students, as they seek to explain the phenomenon of body culture (game, sport, fight, dance, gymnastics, among others) limiting the size technique, the biomechanical movement, biologization of human movement.